2017
DOI: 10.1021/acs.jpcc.7b01733
|View full text |Cite
|
Sign up to set email alerts
|

Inside-Out: The Role of Buried Interfaces in Hybrid Cu2ZnSnS4–Noble Metal Photocatalysts

Abstract: Metal–semiconductor hybrids are a promising architecture for functional nanostructures because they efficiently promote charge separation. The morphology of the hybrid supports two mechanisms of charge generation and transfer, namely, the excitation of electrons to the conduction band of the semiconductor or the induction of surface plasmon resonance on the metal. Here, we compared the photocatalytic activity of nanoparticles with a core–shell or dimer morphology, using Pt, Pd, or Au as the metal and Cu2ZnSnS4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Since in the case of ACN1, a few numbers of metal nanoparticles are embedded into the Cu 3 N NCs (in the case of ACN1), they form buried interface between metal and semiconductor. This buried interface often serves as a defect center, which is responsible for lower photocatalytic activity of ACN1 nanoheterostructures . On the other hand, ACN2 show a prominent plasmonic absorption in the wavelength region 540 nm, which matches with the wavelength range of green LED.…”
Section: Resultsmentioning
confidence: 99%
“…Since in the case of ACN1, a few numbers of metal nanoparticles are embedded into the Cu 3 N NCs (in the case of ACN1), they form buried interface between metal and semiconductor. This buried interface often serves as a defect center, which is responsible for lower photocatalytic activity of ACN1 nanoheterostructures . On the other hand, ACN2 show a prominent plasmonic absorption in the wavelength region 540 nm, which matches with the wavelength range of green LED.…”
Section: Resultsmentioning
confidence: 99%
“…79 The CO served a dual role-it reduced the Pt(acac) 2 on the pre-formed Pt-tip and also dictated the nal {100} faceted tip morphology. Some examples of different adaptations of the abovementioned selective deposition methods of gold and platinum resulted in CdSe pyramids/Au, 80 PbS QDs/Au, 81 PbSe QDs/ multiple-domain(s) and sizes of Au, 82 PbTe nanocubes/Au, 83 Ag 2 Se/Au and Ag 3 AuSe 2 /Au, 84 Cu 2 ZnSnS 4 (CZTS, a Cd-free SC with E g $ 1.5 eV) cubes/Au and /Pt, 85 NRs/Au, 86 core@shell or heterodimers with Pt, Pd and Au, 87 QDs/AuAg, 88 CuInS 2 /Pt, 89 CdSe@CdS NR/Pt, 90 CdSe@CdS NR/Co, 57 CdSe@CdS NR/Ni, 91 Bi 2 S 3 /Au nano-dumbbells, 92 anisotropic quasi-2D CdSe nanosheets or nanoplatelets (NPLs) 70,[93][94][95][96] and related 2D cadmium chalcogenides (e.g., CdS 96,97 and CdSe-CdS core-crown NPLs 94,95 ) with metals such as /Au, 70,[93][94][95]97 /Pt, [93][94][95][96][97] /Pd, 93 metal alloys such as Pt-Au 95 and Ni-Pt, 97 as well as selective deposition of distinguishable Pt and Au domains. 95 The mentioned variations include changes to the shape, size, morphology and material of the starting SC, as well as expansion of the deposited metals and alloys, some of which are reproduced in Fig.…”
Section: Colloidal Routes To Form M/sc Interfacesmentioning
confidence: 99%
“…The effect of incorporating plasmonic and noble Au and noble Pt has been explored as well by Dilsaver et al ., Yu et al . and few other groups . In case of plasmonic as well as noble metal Au, the surface plasmon effect (SPR) helps in the absorption of more radiation through near field effect.…”
Section: Photoelectrochemical and Photocatalytic Applicationsmentioning
confidence: 99%
“…In a study by Sadan et al . it is suggested that the exposed metal‐semiconductor interfaces in dimers perform better than buried interfaces in core‐shell nanomaterials . Other quaternary chalcogenides such as anisotropic kesterite CZTSe, orthorhombic CZGeS, NCs and CFTS microspheres have also displayed strong visible region photon absorption and enable high photocatalytic RhB degradation efficiency under visible‐light illumination ,,.…”
Section: Photoelectrochemical and Photocatalytic Applicationsmentioning
confidence: 99%